Navigating eye health problems of urban slums in Asansol, West Bengal: a comprehensive study - Chakraborty, Kamal Kumari; Dwivedi, Himanshi; Sahu, Ananta Basudev (International Journal Of Community Medicine And Public Health, 2025)
Background: Rapid urbanization in India has expanded slum settlements where residents face multidimensional deprivation and limited access to eye care. Asansol, a fast-growing industrial city in West Bengal, has large, underserved slum populations, but little evidence on their eye-health needs. This feasibility study assessed socio-economic vulnerability, eye-care needs, and gaps in service access to inform an urban eye-care model. Methods: A cross-sectional quantitative study was conducted from March to May 2024 across 20 randomly selected slums of the Asansol Municipal Corporation. Data were collected through a desk review, slum mapping, and household surveys with 378 adults (≥18 years), selected using cluster-based four-segment sampling. A structured questionnaire captured socio-demographics, WASH indicators, ocular symptoms, and care-seeking. A composite Vulnerability Index was developed using four dimensions-industry/employment, housing/sanitation, poverty/unemployment, and healthcare access-integrated with population density and categorized into low, moderate, high, and critical vulnerability. Results: Nearly half of respondents were illiterate, and 90% were engaged in informal employment. Sanitation gaps were pronounced, with 30% lacking toilet access. A total of 65.9% reported household eye problems, most commonly redness (43.8%), blurred vision (42.6%), and itching (24.5%). Despite proximity to facilities, majority had limited or no access to healthcare, and most relied on government hospitals (80.7%). Vulnerability mapping identified 10 slums as high or critical across all domains, highlighting substantial inequities. Conclusions: Urban slum communities in Asansol face high socio-economic vulnerability and substantial unmet eye-care needs. Findings support the feasibility and necessity of localized, affordable, community-based eye-care models integrated within broader urban health and slum development programmes, prioritizing high- and critical-vulnerability slums.